The Lisbon Treaty: A Sinuous Ratification - Adrian-Gabriel Corpadean (CES Working Papers, 2011)
This article deals with the intricate ratification process of the Lisbon Treaty, while focusing on the thorny issues of Euroscepticism and democratic deficit within the European Union in the current institutional context. The study is based on a wide research endeavour, whose purpose has been to encompass multiple points of view on the future of the European Union, seen from the perspective of the Treaty of Lisbon and its reception in all member states. These viewpoints include the ones found in the speciality literature, as well as in the press that published representative articles during the debates on the ratification of the Lisbon Treaty. Useful attempts are made in order to classify the member states of the EU according to various relevant criteria in their attitude germane to the ratification of the Treaty, so as to outline new waves of Euroscepticism, opt-outs and criticism. Apart from an institutional and a legal perspective, this study presents a large number of political, national and even cultural aspects encountered in attitudes and courses of action pertaining to the future of European Construction, seen through the eyes of the reform process carried out by the latest EU major legal document.
Keywords: 330; Lisbon Treaty; reform; Euroscepticism; democratic deficit; ratification